2022
DOI: 10.3934/mbe.2022266
|View full text |Cite
|
Sign up to set email alerts
|

Improving vaccination coverage and offering vaccine to all school-age children allowed uninterrupted in-person schooling in King County, WA: Modeling analysis

Abstract: <abstract> <p>The rapid spread of highly transmissible SARS-CoV-2 variants combined with slowing pace of vaccination in Fall 2021 created uncertainty around the future trajectory of the epidemic in King County, Washington, USA. We analyzed the benefits of offering vaccination to children ages 5–11 and expanding the overall vaccination coverage using mathematical modeling. We adapted a mathematical model of SARS-CoV-2 transmission, calibrated to data from King County, Washington, to simulate scenar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“… 50 Vaccine intervention strategies were studied interventions in 69 studies, and vaccines combined with other strategies (including non-pharmaceutical interventions (NPIs) and screening) in 23 studies. 23 , 27 , 29 , 30 , 31 , 33 , 35 , 36 , 37 , 38 , 39 , 41 , 44 , 45 , 46 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Seventy-three studies used compartmental models, and agent-based models were employed in 19 studies. 23 , 24 , 30 , 32 , 33 , 37 , 39 , 40 , 41 , 43 , 45 , 46 , 50 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Table 1 shows the summary of study characteristics included in this review, and a full description of included studies can be found in Supplementary Table S1 in Supplementary Material.…”
Section: Resultsmentioning
confidence: 99%
“… 50 Vaccine intervention strategies were studied interventions in 69 studies, and vaccines combined with other strategies (including non-pharmaceutical interventions (NPIs) and screening) in 23 studies. 23 , 27 , 29 , 30 , 31 , 33 , 35 , 36 , 37 , 38 , 39 , 41 , 44 , 45 , 46 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Seventy-three studies used compartmental models, and agent-based models were employed in 19 studies. 23 , 24 , 30 , 32 , 33 , 37 , 39 , 40 , 41 , 43 , 45 , 46 , 50 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Table 1 shows the summary of study characteristics included in this review, and a full description of included studies can be found in Supplementary Table S1 in Supplementary Material.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 33 ]), for investigating the effect of lifting social distancincing interventions (e.g. [ 34 36 ]), for now- and forecasting (e.g. [ 37 – 40 ]), for evaluating the use of antivirals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]), for investigating the effect of lifting social distancincing interventions (e.g. [34][35][36]), for now-and forecasting (e.g. [37][38][39][40]), for evaluating the use of antivirals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]), for investigating the effect of lifting social distancincing interventions (e.g. [34][35][36]), for now-and forecasting (e.g. [37][38][39][40]), for evaluating the use of antivirals (e.g.…”
Section: Introductionmentioning
confidence: 99%